A multifunctional use of bis(methylene)bis(5-bromo-2-hydroxyl salicyloylhydrazone): from metal sensing to ambient catalysis of A3 coupling reactions. Issue 67 (9th November 2020) - Peewasan, Krisana; Merkel, Marcel P.; Fuhr, Olaf; Anson, Christopher E.; Powell, Annie K.
Abstract : 3D-complexes of the ligand H6 L = bis(methylene)bis(5-bromo-2-hydroxyl salicyloylhydrazone) not only show promising fluorescence sensing properties but are also effective A3 coupling reagents. Abstract : The potential use of bis(methylene)bis(5-bromo-2-hydroxylsalicyloylhydrazone) as a multifunctional fluorescence sensor for Cu 2+, Ni 2+, Co 2+ and Fe 2+ ions was investigated. The optical behaviour shows an increase in an absorption band at 408 nm which can be ascribed to the d–d transition (UV-vis) of the metal ions and a concomitant decrease in fluorescence intensity at 507 nm. The crystallographic analysis shows the binding site of the sensor to two Cu 2+ ions and confirms the stoichiometry of 1 : 2 (ligand to metal) which is in good agreement with a Job plot analysis. Furthermore the Cu 2+ -complex catalyses A3 coupling reactions at 1 mol% catalytic loading; chiral propargylamine derivatives were obtained in high yield after 24 h reaction time under ambient conditions.